Routes of Transboundary Historical and Ethnographic Tourism in Bukovina - Бучко, Жанна Іванівна (Київський національний університет імені Тараса Шевченка, 2015)
The goal of this paper is to study the prospects of establishing and supporting historical and ethnographic tourist routes at the trans-boundary territory of Chernivtsi region in Ukraine and Suceava region in Romania. (Ethnically and culturally distinct region known as Bukovina) Methodology. Our work relies on systematization and synthesis of the empirical data about practical transboundary tourism projects in Bukovina. Results. The author established general tendencies of transboundary collaboration in such tourism areas as development and introduction of routes in Chernivtsi and Suceava regions. Our paper analyses prior experience in supporting such routs and proposes a network of new routes, formed following the results of a series of field expeditions. We substantiate the development of eight international routes within Bukovina boundary lands and analyze the problems related to functioning of such routes. The scientific novelty of our work is development of transboundary routes in Chernivtsi and Suceava region based on the means of transportation (automobile, bicycle, walking) and the underlying theme (historical or ethnographic). The practical significance of this research is the possibility of implementation of the proposed concepts into the planned tourism activity in accordance with the formal development programs and strategies accepted in Chernivtsi region.

Метою написання статті є вивчення можливостей функціонування та реалізації маршрутів історичного та етнографічного туризму на транскордонній території Чернівецької області України та Сучавського повіту Румунії (етнокультурний регіон відомий як Буковина). Методика роботи полягала в систематизації й синтезі емпіричних даних, що охоплювали практичні транскордонні проекти в галузі туризму на Буковині. Результати. Автором було виявлено загальні тенденції транскордонної співпраці в галузі туризму щодо розробки та впровадження маршрутів територією Чернівецької області та Сучавського повіту. У статті проаналізовано попередній досвід функціонування таких маршрутів та запропоновано мережу нових, укладених за результатами ряду експедиційних польових досліджень. Обґрунтовано розробку восьми міжнародних маршрутів територією Буковинського прикордоння. Проаналізовані проблеми функціонування таких маршрутів. Науковою новизною роботи є розробка транскордонних маршрутів територією Чернівецької області та Сучавського повіту за формою пересування (автомобільні, велосипедні, пішохідні) та тематикою (історичні та етнографічні). Практична значущість дослідження полягає в можливості впровадження отриманих результатів у планову туристичну діяльність відповідно до прийнятих у Чернівецькій області програм та стратегій.
Транскордонні маршрути історико-етнографічного туризму на Буковині
Keywords: transboundary tourism; transboundary tourist routes; transboundary region; historical-ethnographic tourism; транскордонний туризм; транскордонні туристичні маршрути; транскордонний регіон; історико-етнографічний туризм